ECO-CHEMICAL MANAGEMENT OF A NEW FUNGAL ROT (PENICILLIUM FUNICULOSUM THOM.) OF AONLA - S. M. YADAV,; R. K. PATIL,; SAURABH SINGH,; L. P. BALAI,; RAI AJAY KUMAR, (The Bioscan, 2012)
The pathogen was isolated from aonla fruits. The pure culture obtained after re-isolation was sent for identification to I.T.C.C., Division of Mycology and Plant Pathology, Indian Agricultural Research Institute, New Delhi where it was identified as Penicillium funiculosum (ITCC: 7046.08). And it was found first report in India. Eleven fungicides (500 and 1000 ppm) were screened in in vivo, among them significantly lowest Penicillium rot severity was observed in fruits treated with carbendazim at 1000 ppm both in pre (12.49 %) and post-inoculation (12.83 %) followed by benomyl 1000 ppm both in pre (13.49 %) and post inoculation (15.03 %) treatments at 7 days after inoculation. The higher dose (1000 ppm) of fungicides found more effective in reducing the Penicillium rot severity than the lower dose (500 ppm) in pre and post-inoculation. The pre-inoculation treatment found better in controlling the fruit rot than post- inoculation.